Pharmaceutical Chemistry, 2. - Chatwal, Gurdeep R. (Himalaya Pub. House, 2008)
The present text?Pharmaceutical Chemistry? Organic, Vol. II? has been thoroughly revised according to the revised syllabus framed by the Pharmacy Council of India. In this revised edition, the subject matter has been reorganised incorporating application-wise classification(therapeutic, pharmaceutical, etc.) rather than the traditional chemical classification. More stress has been in explaining the medicinal and pharmaceutical terms. Students will find repetition for some medicinal compounds which find more than one application.